Taxonomic revision and cladistic analysis of ghost spiders of the genus Tafana Simon, 1903 (Araneae: Dionycha, Anyphaenidae), with the descriptions of twelve new species - De Oliveira, Luiz Fernando M.; Brescovit, Antonio Domingos (European Journal of Taxonomy, 2021)
The diversity of the genus Tafana Simon, 1903 is poorly known in the Neotropical regions. In this work we provide a taxonomic review of the genus as well as a phylogenetic analysis. The ingroup of the analysis is composed of sixteen species of Tafana and the outgroup is composed of five representatives of Anyphaenidae. The sister-group recovered for Tafana is the clade Aysha + Xiruana, being supported by the embolic process on the male bulb. Two species groups within Tafana are herein proposed, the silhavyi group and the riveti group, based on two exclusive synapomorphies in the male bulb. We redescribe Tafana quelchi and present a description of the previously unknown female of Tafana silhavyi, both from Venezuela. In addition, we describe the first adult specimens of Tafana straminea. Twelve new species, along with several previously described species, are described, illustrated and mapped: T. riveti, T. straminea, T. quelchi, T. kunturmarqa sp. nov., T. humahuaca sp. nov., T. pastaza sp. nov., T. nevada sp. nov., T. huatanay sp. nov. and T. ruizi sp. nov. from the riveti species group; T. maracay sp. nov., T. arawak sp. nov., T. chimire sp. nov. and T. pitieri sp. nov. from the silhavyi species group; T. oliviae sp. nov. from Argentina and T. orinoco sp. nov. from Venezuela, neither of which belongs to any species group. We also discuss the genital morphology of the species groups based on the results of the phylogenetic analysis. Furthermore, distribution maps for all species, including new records for T. riveti, T. straminea and T. quelchi, are presented.